2009
DOI: 10.1111/j.1365-2249.2009.04075.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune response toPlasmodium vivaxhas a potential to reduce malaria severity

Abstract: SummaryPlasmodium falciparum infection causes transient immunosuppression during the parasitaemic stage. However, the immune response during simultaneous infections with both P. vivax and P. falciparum has been investigated rarely. In particular, it is not clear whether the host's immune response to malaria will be different when infected with a single or mixed malaria species. Phenotypes of T cells from mixed P. vivax-P. falciparum (PV-PF) infection were characterized by flow cytometry, and anti-malarial anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…In areas of co-endemicity of multiple malaria parasite species, homologous antigens may elicit cross-reactive antibodies [ 10 12 ]. We detected that 18% of patients with acute P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas of co-endemicity of multiple malaria parasite species, homologous antigens may elicit cross-reactive antibodies [ 10 12 ]. We detected that 18% of patients with acute P .…”
Section: Discussionmentioning
confidence: 99%
“…Interactions occur between different parasite species [ 8 ], and as a result, prior infections by one species influence the course of a subsequent infection by the same or a different species [ 9 ]. Antigens with high levels of homology between malaria parasite species may elicit cross-reactive antibodies targeting more than one parasite species [ 10 12 ]. Thus, antibody responses to individual antigens may evolve differently, depending on the epidemiological settings.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that γδ T cells reduce the severity of malaria in humans [13] and control the chronic parasitaemia of P. chabaudi infection in mice [37]. The cytotoxic role of γδ T cells was shown in vitro using P. falciparum [38], [39], [40], [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that exposure to both parasite species in mixed infections also increases the severity of the disease, although some studies suggest the opposite because of the development of species cross protection (Chuangchaiya et al, 2010; Sutton et al, 2009; Whitehorn et al, 2010). Diagnoses of P. falciparum and P. vivax mixed infection may be difficult as the correct identification of ring forms on Giemsa-stained thick blood smears is not always possible.…”
Section: Current Malaria Problem In Non-amazonian Regions Of Latinmentioning
confidence: 99%